The Effect of Cutaneous Stimulation: Slow Stroke Back Massage on Sleep Quality Improvement in Elderly - Suarilah, Ira; Hayat, Mohammad; Indarwati, Retno (International Journal of Psychosocial Rehabilitation, 2020)
The elderly are susceptible to declining sleep quality. There are several causes of decreased sleep qualities such as; increasing sleep latency, decreasing sleep efficiency, waking up earlier, and unable t o back to sleep. One of t h e non-pharmacological methods, Cutaneous Stimulation: Slow Stroke Back Massage, helps the patient to increase their sleep quality. Moreover, it represents a positive experience of the individual to improve relaxation and sleep quality. This research used a quasi-experimental design. There were 32 elderly who have sleep disorders, become object research of this study. These object research were categorized into two groups (treatment & control). This researches used Total Sampling’s data collection method. Moreover, it used cutaneous stimulation: Slow Stroke Back Massage as an independent variable and improvement of sleep quality as the dependent variable. Besides that, this research uses the Pittsburgh Sleep Quality Index (PSQI) questionnaire to collect the data. Furthermore, it used t he Wilcoxon Sign Rank Test and Mann Whitney Test to analyze significance level α ≤0.05. The result of statistic obtains value p=0.001 (0.001 < 0.05) in Wilcoxon Sign Rank Test and value a=0.000 (0.000 < 0.05) in Mann Whitney Test. The final analysis shows that cutaneous stimulation: Slow Stroke Back Massage affects the improvement of sleep quality an elderly.